2013
DOI: 10.1021/jp407563f
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium-Cyclobutadiene Multidecker Inverse Sandwiches: Electronic Structure and Second-Hyperpolarizability

Abstract: Beryllium forms stable sandwich and inverse sandwich complexes with the cyclobutadiene molecule. Two types of multidecker complexes are designed. Multidecker inverse sandwiches are found to be thermally more stable than the corresponding sandwich complexes. The average distance between two consecutive metals and the two consecutive cyclobutadiene rings increase gradually on increasing size of the chosen inverse sandwich complexes. The density functional theory functionals B3LYP, BHHLYP, BLYP, M06, CAM-B3LYP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…To have an insight into the origin of third–order NLO responses, two–level model of the γ tot is considered for the studied complexes, which is the linkage between the γ tot and electronic transition(s) in low–lying crucial excited states. Therefore, using the two–level models 61 is a reliable way to analyze second hyperpolarizabilities and the expression is as follows: f 2 / E 5 . where f the oscillator strength, and E the transition energy.…”
Section: Resultsmentioning
confidence: 99%
“…To have an insight into the origin of third–order NLO responses, two–level model of the γ tot is considered for the studied complexes, which is the linkage between the γ tot and electronic transition(s) in low–lying crucial excited states. Therefore, using the two–level models 61 is a reliable way to analyze second hyperpolarizabilities and the expression is as follows: f 2 / E 5 . where f the oscillator strength, and E the transition energy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to asymmetric moieties enriched with excess electrons, the first hyperpolarizability can be enhanced such as second-order electric susceptibility per unit volume thus playing a significant role in the second harmonic generation (SHG) process, leading to better NLO responses [6][7][8]. Many stratagems available that are quite useful in fabricating optoelectronic materials with high performances regarding both theoretical and experimental viewpoints such as establishing -conjugated bridge between donor and acceptor moieties (D--A) [9][10][11][12], by approaching bond length alteration (BLA) theory [13], employing multi-decker sandwiching clusters as fabricating units [14,15], and doping or adsorbing alkali metals, transition metals or super alkali on different nanoclusters, are some of the most effective approaches [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that magnesium and beryllium oxide clusters exhibit very promising properties for hydrogen storage materials . Specifically, several theoretical researches revealed that introducing the diffuse excess electron, such as alkali metals, could be an efficient strategy to improve the NLO properties of different systems . It is hoped that such studies can provide at least a semi‐quantitative description of some of the features of these metal clusters, acting as an aid to the unraveling of observed and anticipated complex experimental observations and resulting from novel structural properties.…”
Section: Introductionmentioning
confidence: 99%